Dissolution Enhancement of Gendarusin A by Poloxamer 188 Addition in Justicia gendarussa Burm. f Ethanolic Extract Granule Matrix - Weka Sidha Bhagawan, Bambang Prajogo, Achmad Radjaram (Journal of Applied Pharmaceutical Science, 2017)
Justicia gendarussa Burm. f (Acanthaceae) is often used as folk medicine for many purposes in Indonesian indigenous tribes. Preclinical studies on J. gendarussa leaves indicated that the extract possessed the activity of male contraception. Gendarusin A was found to be the compound responsible for the activity. The purpose of this study was to prove that poloxamer 188 can increase the dissolution rate of gendarusin A in Justicia gendarussa Burm. f ethanolic extract granule (JEG) matrix, in an effort to find male contraceptives phytopharmaceutical product. In this research, we had made three JEG matrix types, which were type 1 (without the addition of surfactant poloxamer 188); type 2 (with the addition of 1% surfactant poloxamer 188), and type 3 (with the addition of 2% surfactant poloxamer 188). The three types of JEG matrix then examined by dissolution test to obtain the dissolution rate of gendarusin A. HPLC instrument was utilized to analyse the concentration of gendarusin A from dissolution mediums. The results showed that the gendarusin A in JEG matrix type 3 dissolved much faster compared to JEG matrix type 1 and type 2. The score of dissolution efficiencies of gendarusin A in JEG matrix type 1, type 2, and type 3 were 15,72%; 24,22%; and 31,83% respectively. It can be concluded that poloxamer 188 addition can increase the dissolution rate of gendarusin A in JEG matrix.
Keywords: Gendarusin A, Justicia gendarussa, Dissolution, Granule, Poloxamer 188.